Composite particles, cathodes and solid-state batteries
By applying a coating film with balanced OH and CO3 groups on positive electrode active material particles in sulfide-based all-solid-state batteries, the interface resistance is reduced, addressing the battery resistance issue and enhancing battery performance.
Patent Information
- Application Number
- JP2022068300
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-18
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-04-18
AI Technical Summary
Sulfide-based all-solid-state batteries face increased battery resistance due to direct contact between positive electrode active material particles and sulfide solid electrolyte, leading to deterioration of the electrolyte.
Composite particles with a coating film containing glass network-forming elements and oxygen are used, where the coating film covers the positive electrode active material particles, forming a balanced interface with the sulfide solid electrolyte to reduce interfacial resistance.
The balanced coating film reduces battery resistance by promoting bond formation while inhibiting the formation of resistive layers, resulting in lower interfacial resistance and improved battery performance.
Smart Images

Figure 0007619319000003 
Figure 0007619319000004 
Figure 0007619319000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to composite particles, positive electrodes, and all-solid-state batteries. [Background technology]
[0002] Japanese Patent Laid-Open Publication No. 2010-135090 (Patent Document 1) discloses a reaction suppressing portion formed at the interface between a positive electrode active material and a solid electrolyte material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-135090 A Summary of the Invention [Problem to be solved by the invention]
[0004] Sulfide-based all-solid-state batteries (hereinafter may be abbreviated as "all-solid-state batteries") have been developed. The all-solid-state battery includes a sulfide solid electrolyte. If the sulfide solid electrolyte comes into direct contact with the positive electrode active material particles, the sulfide solid electrolyte may deteriorate. The deterioration of the sulfide solid electrolyte (ion conduction path) may increase the battery resistance. Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. The coating film prevents direct contact between the positive electrode active material particles and the sulfide solid electrolyte, which may reduce the deterioration of the sulfide solid electrolyte. However, there is room for improvement in the battery resistance.
[0005] An object of the present disclosure is to reduce battery resistance. [Means for solving the problem]
[0006] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0007] 1. The composite particle includes a positive electrode active material particle and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particle. The coating film includes a glass network forming element and oxygen. The composite particles satisfy the relationship of the following formula (1). 0 OH / I CO3 ≦3.0…(1) In the above formula (1), I OH and I CO3 and I respectively indicate the height of the peak in the diffuse reflectance Fourier transform infrared absorption spectrum. OH indicates the height of the peak derived from the OH group. CO3 indicates the height of the peak derived from the CO3 group.
[0008] The resistance at the interface between the coating film and the sulfide solid electrolyte (hereinafter may be abbreviated as "interface resistance") constitutes part of the battery resistance. According to the new findings of the present disclosure, the coating film has OH groups, which may form bonds between the coating film and the sulfide solid electrolyte. The formation of bonds is expected to reduce the interface resistance. However, if there are too many OH groups, a resistive layer may be formed, which may increase the battery resistance instead.
[0009] The coating film may have CO3 groups in addition to OH groups. According to the new findings of the present disclosure, the balance between the amount of bonds formed at the interface and the amount of resistance layer formed may change depending on the quantitative balance between the OH groups and the CO3 groups. The quantitative balance between the OH groups and the CO3 groups may be determined by the peak intensity ratio (height ratio) of the diffuse reflectance infrared Fourier transform (DRIFT) spectrum. When the above formula (1) is satisfied, the formation of the resistance layer may be inhibited and the formation of bonds may be promoted. That is, a reduction in the battery resistance is expected.
[0010] 2. The composite particle described in "1." above may satisfy, for example, at least one of the relationships of the following formulas (2) and (3). 0.01≦I OH ≦0.10…(2) 0.03≦I CO3 ≦0.09…(3)
[0011] By satisfying at least one of the relationships of the above formulas (2) and (3), a reduction in battery resistance is expected.
[0012] 3. In the composite particles described in "1." or "2." above, the glass network-forming element may include, for example, at least one element selected from the group consisting of phosphorus (P), boron (B), silicon (Si), nitrogen (N), sulfur (S), germanium (Ge), and hydrogen (H).
[0013] 4. In the composite particle according to any one of the above items "1." to "3.", the coating film may have a thickness of, for example, 5 to 50 nm.
[0014] 5. The positive electrode contains the composite particles according to any one of the above items "1." to "4." and a sulfide solid electrolyte.
[0015] 6. In the positive electrode described in "5." above, the sulfide solid electrolyte may be composed of, for example, 60% or more of a first conductive phase and the remainder. The remainder includes a second conductive phase and a third conductive phase. The first conductive phase includes a crystalline phase of PS4. The second conductive phase includes an amorphous phase of PS4. The third conductive phase includes a crystalline phase of P2S6.
[0016] By ensuring that the composition ratio of the first conductive phase is 60% or more, a reduction in battery resistance is expected.
[0017] 7. The all-solid-state battery comprises the positive electrode described in "5." or "6." above.
[0018] All-solid-state batteries can have low battery resistance because of the small interfacial resistance.
[0019] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief description of the drawings]
[0020] [Figure 1] Figure 1 is an example of a DRIFT spectrum. [Diagram 2] FIG. 2 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram showing the all-solid-state battery in this embodiment. [Figure 4] FIG. 4 is a graph showing the relationship between IOH / ICO3 and initial resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of" are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0022] "At least one of A and B" includes "A or B" as well as "A and B." "At least one of A and B" can also be written as "A and / or B."
[0023] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0024] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0025] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0026] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0027] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.
[0028] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0029] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0030] The term "glass network forming element" refers to an element that has glass-forming ability. The term "glass-forming ability" refers to the ability of the target element to form an oxide glass having a network structure by bonding with oxygen (O).
[0031] <DRIFT spectrum measurement> The DRIFT spectrum can be measured by the following procedure. A sample is prepared. The sample consists of composite particles. The sample does not contain KBr. KBr contains OH groups, which may affect the measurement results. The sample is placed in the measurement device. The measurement device and measurement conditions are as follows. However, the measurement device is only an example and may be substituted by an equivalent device.
[0032] Measurement equipment (Fourier transform infrared spectrophotometer and diffuse reflectance attachment): FT-IR / DR-500, manufactured by JASCO Corporation Accumulation count: 256 Spectral resolution: 4cm -1
[0033] Figure 1 is an example of a DRIFT spectrum. The peaks due to OH groups are, for example, 3300 to 2550 cm -1 can appear in the range of The peaks due to the CO3 group are, for example, at 1600 to 1400 cm-1 can appear in the range of The peaks due to Me-O bonds are, for example, 1210 to 980 cm -1 The DRIFT spectrum in FIG. 1 includes a peak due to a Ni-O bond as an example of a peak due to a Me-O bond.
[0034] <XPS spectrum measurement> The coverage is determined from an XPS (X-ray Photoelectron Spectroscopy) spectrum. The XPS spectrum can be measured by the following procedure: A measuring device is prepared. A sample (composite particles) is set in the measuring device. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. The measurement data is analyzed to determine the element ratio of each element from the peak areas of C1s and O1s. The element ratio of Z is determined from the peak area originating from the glass network forming element (Z). For example, peak areas of P2p, B1s, etc. can be measured. The coverage rate is calculated using the following formula (4). Θ={Z / (Z+O+C+Me)}×100…(4) Θ indicates the coverage rate (%). Z, O, C, and Me indicate the element ratio of each element. When the coating film contains multiple types of Z, the sum of the element ratios is considered to be the element ratio of Z. For example, when the coating film contains P and B, the element ratio of Z is calculated by the formula "Z=P+B". Me indicates a constituent element of the positive electrode active material particles, and is an element other than Li and O. Me may include at least one selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), and aluminum (Al), for example. Depending on the element, for example, Me2p 3 / 2 (or Me2p) peak area can be measured. When Me contains multiple elements, the sum of the element ratios is regarded as the element ratio of Me. For example, when the positive electrode active material particles contain Ni, Co, and Mn, the element ratio of Me is calculated by the formula "Me = Ni + Co + Mn".
[0035] The measuring devices are shown below. However, these are merely examples and may be substituted with equivalent devices. Measurement device: Product name "PHI X-tool", manufactured by ULVAC-PHI Analysis software: Product name "MulTiPak", manufactured by ULVAC-PHI, Inc.
[0036] <NMR spectrum measurement> The composition ratio of the first conductive phase in the sulfide solid electrolyte is calculated by the following formula (5). R1 = {I1 / (I1+I2+I3)} × 100 … (5) R1 (%) indicates the constituent ratio of the first conductive phase. I1, I2, and I3 are measured by magic angle spinning phosphorus-31 nuclear magnetic resonance ( 31 P Magic Angle Spinning Nuclear Magnetic Resonance, 31 It is measured by P MAS NMR. I1 is 31 In the P MAS NMR spectrum, the area (integral value) of the peak at a chemical shift of 78 ppm, the area of the peak at a chemical shift of 83.7 ppm, and the area of the peak at a chemical shift of 92 ppm are shown. The peak at 78 ppm is thought to correspond to PS42b. The peak at 92 ppm is thought to correspond to PS44d. I2 is 31 In the P MAS NMR spectrum, the sum of the areas of the peaks at a chemical shift of 85 ppm and 88 ppm is shown. I3 is 31 In the P MAS NMR spectrum, the area of the peak at a chemical shift of 106 ppm is shown.
[0037] same 31 Based on the P MAS NMR spectrum, the composition ratio (R2) of the second conductive phase (low ion conductive phase) in the sulfide solid electrolyte is calculated by the following formula (6). R2 = {I2 / (I1+I2+I3)} × 100 … (6) Furthermore, the composition ratio (R3) of the third conductive phase (low ion conductive phase) in the sulfide solid electrolyte is calculated by the following formula (7). R3 = {I2 / (I1+I2+I3)} × 100…(7)
[0038] 31 The conditions for P MAS NMR spectrum measurement may be as follows. The measurement device is an example. An equivalent device may be used instead. Measurement device: "AVANCE III 600", manufactured by Bruker Observation frequency: 242.94MHz Observation width: 250kHz Measurement method: Single pulse method Flip angle: 90° pulse Repeated waiting time: 5 times or more than T1 Probe: 4.0mm MAS rotation speed: 15kHz Chemical shift standard: 85% phosphoric acid aqueous solution (0 ppm)
[0039] <Film thickness measurement> The thickness (film thickness) of the coating film can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the thicknesses at 200 points in total is regarded as the film thickness.
[0040] A "hollow particle" refers to a particle in which the area of the cavity in the center is 30% or more of the cross-sectional area of the entire particle in a cross-sectional image (e.g., SEM image). A "solid particle" refers to a particle in which the area of the cavity in the center is less than 30% of the cross-sectional area of the entire particle in a cross-sectional image.
[0041] <Composite particles> FIG. 2 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 100 may be referred to as, for example, a "coated positive electrode active material". The composite particle 100 includes positive electrode active material particles 110 and a coating film 120. The composite particle 100 may form, for example, an aggregate. That is, one composite particle 100 may include two or more positive electrode active material particles 110. The composite particle 100 may have, for example, a D50 of 1 to 50 μm, a D50 of 1 to 20 μm, or a D50 of 5 to 15 μm.
[0042] <Coating film> The coating film 120 is a shell of the composite particle 100. The coating film 120 covers at least a portion of the surface of the positive electrode active material particle 110. The coating film 120 can inhibit contact between the positive electrode active material particle 110 and the sulfide solid electrolyte.
[0043] The coating film 120 may have a thickness of, for example, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm.
[0044] The coverage may be, for example, 80 to 100%, 90 to 100%, or 95 to 100%.
[0045] The coating film 120 contains a glass network forming element and oxygen. The glass network forming element may contain, for example, at least one selected from the group consisting of P, B, Si, N, S, Ge, and H. The glass network forming element may contain, for example, at least one selected from the group consisting of P and B.
[0046] The glass network forming element and oxygen may form an oxide glass. That is, the coating film 120 may contain an oxide glass having a network structure. The oxide glass may contain, for example, a phosphate skeleton and a borate skeleton. That is, the coating film 120 may contain, for example, at least one selected from the group consisting of a phosphate skeleton and a borate skeleton. For example, in TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) of the composite particle 100, PO2 - , PO3 - When a fragment such as BO2 is detected, the coating film 120 is deemed to contain a phosphate backbone. - , BO3 - When a fragment such as is detected, the coating film 120 is deemed to contain a boric acid backbone.
[0047] The coating film 120 may further contain, for example, lithium (Li) etc. The composite particle 100 may satisfy, for example, the relationship of the following formula (8). C Li / C z ≦2.5…(8) C Li , C z indicates the element ratio measured by XPS. Li indicates the element ratio of Li. C z indicates the element ratio of the glass network forming element. When the coating film 120 contains a plurality of glass network forming elements, C z C represents the total element ratio of each glass network forming element. Li / C z It is considered that C reflects the Li composition ratio in the coating film 120. Li / C z When C is 2.5 or less, a reduction in battery resistance is expected. Li / C z may be, for example, 1 or less, or 0.5 or less.
[0048] The coating film 120 may contain OH groups (hydroxyl groups) and CO3 groups (carbonate groups). For example, OH groups and CO3 groups may be present on the surface of the coating film 120. The OH groups and CO3 groups satisfy a specific quantitative balance. That is, in the DRIFT spectrum, OH / I CO3 is greater than 0 and less than or equal to 3.0 (see formula (1) above). This is expected to inhibit the formation of a resistive layer at the interface between the coating film 120 and the sulfide solid electrolyte, and to promote the formation of a bond. OH / I CO3 may be, for example, 1.4 or less, or 1.0 or less. OH / I CO3 may be, for example, 1.0 or more, or 1.4 or more.
[0049] I OH may be, for example, 0.01 to 0.10 (see formula (2) above). OH may be, for example, 0.07 or more, or 0.08 or less.
[0050] I CO3 may be, for example, 0.03 to 0.09 (see formula (3) above). CO3 may be, for example, 0.05 or more, or 0.07 or less.
[0051] 《Cathode active material particles》 The positive electrode active material particle 110 is a core of the composite particle 100. The positive electrode active material particle 110 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 110 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm. The positive electrode active material particle may be, for example, a hollow particle. The positive electrode active material particle may be, for example, a solid particle.
[0052] The positive electrode active material particles 110 may contain any component. The positive electrode active material particles 110 may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 Li(NiCoAl)O2 may contain, for example, LiNi 0.8 Co 0.15 Al 0.05 It may contain O2, etc.
[0053] The DRIFT spectrum may also include information on the positive electrode active material particle 110. The DRIFT spectrum may include, for example, a peak derived from an Me-O bond. Me represents a constituent element of the positive electrode active material particle 110. Me may include, for example, at least one element selected from the group consisting of Ni, Co, Mn, and Al. Me may be, for example, Ni. The composite particle 100 may satisfy, for example, the relationship of the following formula (9). When the relationship of the following formula (9) is satisfied, the battery resistance may be reduced. 0.02≦I OH / I Ni-O ≦0.29…(9) I Ni-O indicates the height of the peak derived from Ni-O bonds. OH / I Ni-Omay be, for example, 0.21 or less, or 0.19 or less. OH / I Ni-O may be, for example, 0.06 or more.
[0054] The composite particle 100 may, for example, satisfy the relationship of the following formula (10): When the relationship of the following formula (10) is satisfied, the battery resistance may be reduced. 0.10≦I CO3 / I Ni-O ≦0.46…(10) I CO3 / I Ni-O may be, for example, 0.26 or less, or 0.21 or less. CO3 / I Ni-O may be, for example, 0.13 or more.
[0055] Method for forming composite particles The composite particles 100 may be formed by any method. For example, the composite particles 100 may be formed by a spray drying method.
[0056] A coating liquid is prepared. The coating liquid includes a solute and a solvent. The solute includes a raw material of the coating film 120. The solute may include, for example, a phosphoric acid compound, a boric acid compound, a lithium compound, or the like. The solute may include, for example, at least one selected from the group consisting of orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, orthoboric acid, metaboric acid, lithium hydroxide, and lithium nitrate. The solvent may include any component as long as the solute can be dissolved in the solvent. The solvent may include, for example, water, an organic solvent, or the like.
[0057] A suspension can be formed by dispersing the positive electrode active material particles 110 in a coating liquid. The suspension is sprayed by a spray dryer. The coating liquid attached to the surface of the positive electrode active material particles 110 is dried in hot air to form a coating film 120. That is, the composite particle 100 can be formed. After the formation of the composite particle 100, the composite particle 100 may be subjected to a heat treatment. The heat treatment can also be referred to as "calcination."
[0058] The quantitative balance between the OH groups and the CO3 groups can be adjusted, for example, by the following conditions: The following conditions can be combined so that the composite particle 100 that satisfies the above formula (1) is formed.
[0059] For example, the quantitative balance between the OH group and the CO3 group may be adjusted by the solvent composition of the coating liquid. For example, the quantitative balance between the OH group and the CO3 group may be adjusted by the mixing ratio of water and the organic solvent in the coating liquid.
[0060] For example, the quantitative balance between OH groups and CO3 groups may be adjusted by the solute composition in the coating liquid. For example, the quantitative balance between OH groups and CO3 groups may be adjusted by the amount of lithium hydroxide (LiOH) added.
[0061] For example, the coating liquid may be diluted immediately before use. The coating liquid may be diluted to a solid content of 50% or more. The solid content indicates the total mass fraction of components other than the solvent. The quantitative balance between OH groups and CO3 groups may be adjusted by diluting the coating liquid.
[0062] For example, the quantitative balance between OH groups and CO3 groups may be adjusted by the drying conditions of a spray dryer, for example, the drying temperature may be adjusted within the range of 80 to 400°C.
[0063] For example, the quantitative balance between OH groups and CO3 groups may be adjusted by the heat treatment (calcination) conditions after the spray drying process. For example, the calcination temperature may be adjusted within the range of 80 to 300°C.
[0064] <All-solid-state battery> 3 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 200 includes a power generating element 250. The all-solid-state battery 200 may include, for example, an exterior body (not shown). The exterior body may house the power generating element 250. The exterior body may have any shape. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a case made of metal.
[0065] The all-solid-state battery 200 may include a single power generating element 250, or may include a plurality of power generating elements 250. The plurality of power generating elements 250 may form, for example, a series circuit or a parallel circuit.
[0066] The power generating element 250 includes a positive electrode 210, a solid electrolyte layer 230, and a negative electrode 220. That is, the all-solid-state battery 200 includes the positive electrode 210, the solid electrolyte layer 230, and the negative electrode 220.
[0067] 《Positive electrode》 The positive electrode 210 is layered. The positive electrode 210 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, an Al foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0068] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the solid electrolyte layer 230. The positive electrode active material layer includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above. The positive electrode active material layer may further include a conductive material, a binder, and the like.
[0069] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte may contain, for example, Li, P, and S. The sulfide solid electrolyte may further contain, for example, O, Si, etc. The sulfide solid electrolyte may further contain, for example, a halogen, etc. The sulfide solid electrolyte may further contain, for example, iodine (I), bromine (Br), etc. The sulfide solid electrolyte may be, for example, a glass ceramic type or an argyrodite type. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0070] For example, "LiI-LiBr-Li3PS4" refers to a sulfide solid electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 can be produced, for example, by mixing Li2S and P2S5 in a molar ratio of Li2S / P2S5=75 / 25.
[0071] The main phase of the sulfide solid electrolyte may have high ionic conductivity. For example, the sulfide solid electrolyte may be composed of 60% or more of a first conductive phase and the remainder. The remainder includes a second conductive phase and a third conductive phase. The remainder may further include, for example, inevitable impurities. An example of the composition ratio is shown in Table 1 below.
[0072] [Table 1]
[0073] The composition ratio in Table 1 above is as follows: 31 It is determined by the P MAS NMR spectrum and the above formulas (5) to (7). The first measurement example is an example of the measurement result of a glass ceramic. The second measurement example is an example of the measurement result of a ceramic. The glass ceramic may contain an amorphous phase of PS4 and a crystalline phase of P2S6 in addition to the crystalline phase of PS4. The ceramic is substantially composed of the crystalline phase of PS4.
[0074] The first conductive phase includes a crystal phase of PS4. The first conductive phase may be composed of a crystal phase of PS4. The first conductive phase may have high ionic conductivity. The higher the composition ratio of the first conductive phase, the more reduced the diffusion resistance is expected. Furthermore, the crystal phase of PS4 tends to bond easily with OH groups. The composition ratio of the first conductive phase may be, for example, 61.6% or more, 70% or more, 80% or more, 90% or more, or 100%.
[0075] The second conductive phase includes an amorphous phase of PS4. The second conductive phase may be composed of an amorphous phase of PS4. The second conductive phase may have low ionic conductivity. The composition ratio of the second conductive phase may be, for example, 31.7% or less, 20% or less, 10% or less, or 0%.
[0076] The third conductive phase includes a P2S6 crystalline phase. The third conductive phase may be composed of a P2S6 crystalline phase. The third conductive phase may have low ionic conductivity. The composition ratio of the third conductive phase may be, for example, 6.2% or less, 6% or less, 3% or less, 1% or less, or 0%.
[0077] The sulfide solid electrolyte may be, for example, composed of a first conductive phase and unavoidable impurities. The sulfide solid electrolyte may be, for example, composed of a first conductive phase and the remainder being a second conductive phase and unavoidable impurities. The sulfide solid electrolyte may be, for example, composed of a first conductive phase and the remainder being a third conductive phase and unavoidable impurities. The sulfide solid electrolyte may be, for example, composed of a first conductive phase and the remainder being a second conductive phase, a third conductive phase and unavoidable impurities.
[0078] The positive electrode active material layer may further include, for example, a conductive material. The conductive material can form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black (CB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF).
[0079] The positive electrode active material layer may further include, for example, a binder. The binder can bind solid materials together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), butadiene rubber (BR), and polytetrafluoroethylene (PTFE).
[0080] 《Negative electrode》 The negative electrode 220 is layered. The negative electrode 220 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, copper (Cu) foil, nickel (Ni) foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0081] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the solid electrolyte layer 230. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode mixture may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode mixture and the positive electrode mixture. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, SiO x (0 <x<2)、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0082] 《Solid electrolyte layer》 The solid electrolyte layer 230 may also be referred to as a separator. The solid electrolyte layer 230 is interposed between the positive electrode 210 and the negative electrode 220. The solid electrolyte layer 230 separates the positive electrode 210 from the negative electrode 220. The solid electrolyte layer 230 includes a sulfide solid electrolyte. The solid electrolyte layer 230 may further include a binder. Between the solid electrolyte layer 230 and the positive electrode 210, the sulfide solid electrolyte may be the same type or different types. Between the solid electrolyte layer 230 and the negative electrode 220, the sulfide solid electrolyte may be the same type or different types. EXAMPLES
[0083] <Sample preparation> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 6 were produced as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1".
[0084] <No.1> <<Preparation of the positive electrode>> A phosphoric acid solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Furthermore, lithium nitrate was dissolved in the phosphoric acid solution so that the molar ratio of Li to P was 3, thereby preparing a coating liquid.
[0085] Positive electrode active material particles: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (hereinafter may be abbreviated as "NCM") was prepared. NCM was a hollow particle. A suspension was prepared by dispersing 50 parts by mass of a powder of positive electrode active material particles in 53.7 parts by mass of a coating liquid. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The composite particles were heat-treated in air. The heat treatment temperature was 200° C. and the heat treatment time was 5 hours. The composite particles are considered to include positive electrode active material particles and a coating film. The DRIFT spectrum of the composite particles was measured by the above-mentioned method. The DRIFT spectra of Nos. 1 to 6 are shown in FIG. 1.
[0086] The following materials were prepared: Sulfide solid electrolyte: LiI-Li2S-P2S5 (glass ceramic type, D50 = 0.8 μm) Conductive material: VGCF Binder:BR Dispersion medium: heptane Positive electrode current collector: Aluminum foil
[0087] A slurry was prepared by mixing the composite particles, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium. The mixing ratio of the composite particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 7 / 3 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 0.7 parts by mass for 100 parts by mass of the composite particles. The slurry was thoroughly stirred by an ultrasonic homogenizer (product name "UH-50", manufactured by SMT). The slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100 °C for 30 minutes by a hot plate. In this way, a positive electrode raw sheet was manufactured. A disk-shaped positive electrode was cut out from the positive electrode raw sheet. The area of the positive electrode was 1 cm2.2 It was.
[0088] <<Preparation of the negative electrode>> The following materials were prepared: Negative electrode active material particles: Li4Ti5O 12 (D50=1μm) Sulfide solid electrolyte: LiI-Li2S-P2S5 (glass ceramic type, D50 = 0.8 μm) Conductive material: VGCF Binder:BR Dispersion medium: heptane Negative electrode current collector: Cu foil
[0089] A slurry was prepared by mixing a sulfide solid electrolyte, a conductive material, a binder, and a dispersion medium using a stirring device (Filmix (registered trademark) "Model 30-L", manufactured by Primix Corporation). The stirring speed (rotation speed) was 2000 rpm, and the stirring time was 30 minutes. After stirring for 30 minutes, negative electrode active material particles were added to the slurry, and the slurry was further stirred. The stirring speed was 15000 rpm, and the stirring time was 60 minutes.
[0090] The mixing ratio of the negative electrode active material particles and the sulfide solid electrolyte was "negative electrode active material particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 1 part by mass per 100 parts by mass of the negative electrode active material particles. The amount of the binder was 2 parts by mass per 100 parts by mass of the negative electrode active material particles.
[0091] The slurry was applied to the surface of the negative electrode current collector to form a coating film. The coating film was dried at 100°C for 30 minutes on a hot plate. In this way, a negative electrode blank was produced. A disk-shaped negative electrode was cut out from the negative electrode blank. The area of the negative electrode was 1 cm. 2 It was.
[0092] <<Preparation of solid electrolyte layer>> The following materials were prepared: Sulfide solid electrolyte: LiI-Li2S-P2S5 (glass ceramic type, D50=2.5μm)
[0093] A ceramic cylindrical jig was prepared. The area of the hollow cross section (cross section perpendicular to the axial direction) was 1 cm 2 The sulfide solid electrolyte powder was filled into the cylindrical jig. The powder was smoothed. The sulfide solid electrolyte was pressed in the cylindrical jig to form a solid electrolyte layer. The pressure for pressing was 1 ton / cm. 2 It was.
[0094] "assembly" A laminate was formed by stacking the positive electrode, the solid electrolyte layer, and the negative electrode in a cylindrical jig. The solid electrolyte layer was disposed between the positive electrode and the negative electrode. The laminate was pressed to form a power generating element. The pressure for pressing was 6 ton / cm. 2 Two stainless steel rods were inserted into the cylindrical jig so as to sandwich the power generating element. The stainless steel rods were restrained so that a load of 1 ton was applied to the power generating element. The stainless steel rods could function as terminals. In this way, an all-solid-state battery was produced.
[0095] <No.2> A phosphoric acid solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Furthermore, a coating solution was prepared by dissolving lithium hydroxide monohydrate in the phosphoric acid solution so that the molar ratio of Li to P was 0.45. NCM was prepared as the positive electrode active material particles. The NCM was a solid particle. Except for these, the composite particles, positive electrode, and all-solid-state battery were manufactured in the same way as No. 1.
[0096] <No.3> A coating solution was prepared in the same manner as in No. 2. NCM (hollow particles) was prepared as the positive electrode active material particles. In No. 2, the coating solution was diluted with ion-exchanged water immediately before use. Except for these, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1.
[0097] <No.4> Composite particles, positive electrodes, and all-solid-state batteries were produced in the same manner as in No. 3, except that the supply air temperature of the spray dryer was changed to 80°C.
[0098] <No.5> A phosphoric acid solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. A coating solution was prepared by dissolving boric acid (manufactured by Nacalai Tesque, Inc.) in the phosphoric acid solution so that the molar ratio of B to P was 1.0. Except for these, composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 1.
[0099] <No.6> Composite particles, positive electrodes, and solid-state batteries were fabricated in the same manner as in No. 4, except that the coating solution was not diluted.
[0100] <Evaluation> The initial capacity of the all-solid-state battery (hereinafter also referred to as the "cell") was confirmed. The charge and discharge conditions were as follows: Charging: constant current-constant voltage method, rate = 1 / 3C Discharge: constant current, rate = 1 / 3C
[0101] After checking the initial capacity, the SOC of the cell was adjusted to 40%. The cell was discharged for 5 seconds at a rate of 2C. The initial resistance was calculated from the voltage drop after 5 seconds. The initial resistances in Table 2 below are relative values. The initial resistance of No. 2 is defined as "1". The initial resistances of the other samples are expressed as a ratio to the initial resistance of No. 2.
[0102] After measuring the initial resistance, the cell was stored in a thermostatic chamber at 60°C for 14 days. During storage, the positive electrode potential was 4.5V vs. Li / Li + The cells were trickle-charged to maintain the initial resistance. After 14 days, the resistance after endurance was measured under the same conditions as the initial resistance. The resistance increase ratio was calculated by dividing the resistance after endurance by the initial resistance.
[0103] [Table 2]
[0104] <Result> Figure 4 shows the I OH / I CO3 1 is a graph showing the relationship between the initial resistance and the OH / I CO3 When the ratio is 3.0 or less, the initial resistance tends to be significantly reduced. This is believed to be because the formation of a resistive layer is inhibited and the formation of a bond is promoted at the interface between the coating film and the sulfide solid electrolyte.
[0105] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0106] 100 composite particle, 110 positive electrode active material particle, 120 coating film, 200 all-solid-state battery, 210 positive electrode, 220 negative electrode, 230 solid electrolyte layer, 250 power generation element.
Claims
1. Positive electrode active material particles; A coating film; Including, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains a glass network forming element and oxygen, The following formula (1): 0.1<I OH / I CO3 ≦3.0…(1) and further The following formula (2): 0.01≦IOH≦0.10…(2) and The following formula (3): 0.03≦I CO3≦0.09…(3) At least one of the following relationships is satisfied: In the above formulas (1) to (3), I OH and I CO3 indicate the height of a peak in the diffuse reflectance Fourier transform infrared absorption spectrum, I OH indicates the height of the peak derived from the OH group, I CO3 CO 3 The height of the peak derived from the group is shown. composite particles.
2. The glass network forming element includes at least one element selected from the group consisting of phosphorus, boron, silicon, sulfur, and germanium. The composite particle according to claim 1 .
3. The coating film has a thickness of 5 to 50 nm. The composite particle according to claim 1 .
4. The composite particle according to any one of claims 1 to 3 and a sulfide solid electrolyte are included. Positive electrode.
5. The sulfide solid electrolyte comprises 60% or more of a first conductive phase and the remainder, the remainder includes a second conductive phase and a third conductive phase; The first conductive phase is PS 4 The crystal phase of The second conductive phase is PS 4 containing an amorphous phase of The third conductive phase is P 2 S 6 The crystalline phase of The positive electrode according to claim 4 .
6. The positive electrode according to claim 4, All-solid-state battery.
Citation Information
Patent Citations
All-solid battery
JP2010135090A
Positive electrode active material for rechargeable battery with nonaqueous electrolyte, and method for manufacturing the same
WO2007142275A1